Risk assessment for Listeria monocytogenes in traditionally processed fish from informal markets in Accra and Tema - Bomfeh, K. (University of Ghana, 2011)
Traditionally processed fish contributes significantly to food and nutrition security in Ghana. The processing and handling has however been associated with unsanitary and unhygienic practices with documented occurrence of food-borne pathogens. The products are also mainly sold on informal markets, where earlier studies reported the occurrence of Listeria monocytogenes in products sold therein. This study sought to determine the occurrence of L. monocytogenes in traditionally processed (smoked, dried, salted) fish sold on informal markets and to assess the exposure of consumers to the pathogen and the associated risk of illness. The study was based on the Codex Alimentarius protocol for microbial risk assessment. Surveys were conducted on selected traditional processors and consumers to determine processing practices and consumption patterns (frequency and portion sizes) respectively. Samples of traditionally processed fish were procured from some processors and consumer markets in the survey locations for microbial analysis to determine the occurrence and concentrations of L. monocytogenes in the processed fish. Microbial challenge tests were also done by cooking deliberately-contaminated fish for short and long time intervals to determine the survival of the pathogen during domestic cooking. Data from the survey (quantities of fish often consumed) and the laboratory analyses (microbial load) were used to assess the exposure of consumers to the pathogen, and also fitted to parametric (probability) functions to characterize the dose response using Monte Carlo simulations with the @Risk software (version 5.5, Palisade Corporation). Prevalence of L. monocytogenes in the fish products sampled from the markets was high (40-80%). However, the pathogen was not detected in smoked fish sampled immediately after processing, suggesting that post-processing contamination occurred. The concentrations of the pathogen in the products were generally low (102-3 CFU/g), and decreased from smoked fish through to sundried fish. The pathogen also survived in fish used for the challenge test. The estimated risks of illness were low, ranging from 1 in 100 to 1 in 100,000,000,000 chances of illness. Higher risks of illness were recorded for consumption of smoked fish than for sundried fish and salted fish, in that order. Consumers with high susceptibility to L. monocytogenes infection (elderly, children and pregnant women) were at a greater risk of illness than low risk individuals (non-pregnant adults aged 18 – 39 years). The findings suggest that consumers are exposed to ingesting L. monocytogenes through consumption of traditionally processed fish on informal markets. However the risk of illness is low. Improvements in hygienic processing and post-processing handling of fish as well as proper cooking of the fish products before consumption are recommended.